2020
DOI: 10.3390/lubricants8090090
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study on Roughness-Induced Adhesion Enhancement in a Sphere with an Axisymmetric Sinusoidal Waviness Using Lennard–Jones Interaction Law

Abstract: Usually, roughness destroys adhesion and this is one of the reasons why the “adhesion paradox”, i.e. a “sticky Universe”, is not real. However, at least with some special type of roughness, there is even the case of adhesion enhancement, as it was shown clearly by Guduru, who considered the contact between a sphere and a wavy axisymmetric single scale roughness, in the limit of short-range adhesion (JKR limit). Here, the Guduru’s problem is numerically solved by using the Boundary Element Method (BEM) with Len… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Also, Guduru effect only holds for a quite special waviness (single scale, axisymmetric), when the contact area "peels" quite uniformly around a circle and requires the initial contact area to be compact. This poses some limits to the amplitude of roughness, hence, the amplification factor that can be reached (see a more general numerical solution using Lennard-Jones force-separation law in Papangelo and Ciavarella [33]). Regarding the non-axisymmetric effect, Li et al [34] numerical experiments for the pull-off of a sphere in contact with an elastic substrate with 2-dimensional wavy roughness, showed that the adhesion enhancement is further much reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Guduru effect only holds for a quite special waviness (single scale, axisymmetric), when the contact area "peels" quite uniformly around a circle and requires the initial contact area to be compact. This poses some limits to the amplitude of roughness, hence, the amplification factor that can be reached (see a more general numerical solution using Lennard-Jones force-separation law in Papangelo and Ciavarella [33]). Regarding the non-axisymmetric effect, Li et al [34] numerical experiments for the pull-off of a sphere in contact with an elastic substrate with 2-dimensional wavy roughness, showed that the adhesion enhancement is further much reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Although Eq. (4) would predict unbounded enhancement for large roughness amplitude h, the enhancement can only appear up to a certain amplitude, above which internal cracks appear within the contact area (see Papangelo and Ciavarella [32] for a numerical solution).…”
Section: The Guduru's Theory and Experimentsmentioning
confidence: 99%
“…Especially for the limit case of the Guduru geometry, see Papangelo and Ciavarella[32] 5. Notice that PT had already derived Eq (14).…”
mentioning
confidence: 97%
“…Kesari & Lew [29] also showed theoretically how a model wavy rough surface can enhance effective adhesion as a result of mechanical instabilities. Ciavarella and Papangelo [30,31] similarly studied how rough surfaces can actually enhance adhesion for soft solids. This finding is different from the general rule that rough surfaces attenuate adhesion [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%